PROSEDUR PELAPORAN IURAN UPAH TENAGA KERJA PADA PROGRAM JAMINAN SOSIAL TENAGA KERJA DI BPJS KETENAGAKERJAAN CABANG MEDAN KOTA - Anggraini, Nadia; ., Nurlaila (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2021)
Reporting wage contributions to the Jamsostek program is a critical engagement issue that participants need to understand. It is related to the number of benefits that workers will receive because the management uses the contribution to determine the amount of compensation and provide guarantees for their claims. Therefore, honesty and discipline on the employer's part are required when reporting posts and labor productivity. This type of research is descriptive qualitative research, used primary data and secondary data. Data were collected through observation, interviews, and documentation. The data analysis used in this research is descriptive and uses relevant, accurate, and timely variables. The results showed that: a) BPJS Ketenagakerjaan Medan Kota branch mentions cash or cash receipts from its business income by reporting labor wage contributions. b) The reporting of labor wage contributions carried out by the Medan City branch of BPJS Ketenagakerjaan is already good. The Medan City branch of the BPJS Ketenagakerjaan can divide the contribution report function into four functions, namely administrative functions, financial functions, technology, and information functions, and marketing functions. c) The Medan City branch BPJS Ketenagakerjaan implements all incoming cash receipts, documents, or forms arranged based on the NPP and all contribution receipts either through postal giro or the company directly deposited the bank immediately every day